Pengembangan E-Bahan Ajar Berbantuan Augmented Reality Pada Mata Pelajaran IPAS Materi Keanekaragaman Budaya - Ferdyan Hanif Katsirun Nawwal; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop, test the feasibility, effectiveness, and practicality of augmented reality (AR)-based e-learning materials in improving student learning outcomes. This study is a development research (R&D) using the Borg and Gall model involving 42 fifth grade students of Podorejo 02 Elementary School in the 2024/2025 academic year. Data collection was carried out through test techniques (pretest - posttest) and non-test. The results of the validation of material, language, and media experts showed that the media was very feasible to use. Positive responses from teachers and students to the practicality of the media, with a high level of satisfaction. The effectiveness of the media was proven by the t-test which showed significant results (0.000 <0.05) and an increase in learning outcomes (N-gain) in the “moderate” category. The results of the study indicate that e-teaching materials assisted by AR meet the criteria of being feasible, practical, and effective in improving learning outcomes in science learning for grade V at SD Negeri Podorejo 02.